If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8h + 9 + -5h = 74 Reorder the terms: 9 + -8h + -5h = 74 Combine like terms: -8h + -5h = -13h 9 + -13h = 74 Solving 9 + -13h = 74 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -13h = 74 + -9 Combine like terms: 9 + -9 = 0 0 + -13h = 74 + -9 -13h = 74 + -9 Combine like terms: 74 + -9 = 65 -13h = 65 Divide each side by '-13'. h = -5 Simplifying h = -5
| 725x+10.5=19.50x | | 7(-3x^3)= | | 2w-4x-y+5w+16x-4y= | | lx-1l=-8 | | 14x+34y=1 | | 9x-3y+12w+2y-5w+3x= | | 8xsquared+10x-7=0 | | -2+12=13x-5-12x | | 36x-49=0 | | log(2)=3 | | X+0.03X=39140 | | 10y-2=7y+7 | | 4x+1=2(x+2) | | F(x)=4x^2+34x+16 | | .5(3x)=8(2) | | 3t^2=13t+10 | | 8(5+x)=16 | | 5x-22x-15=0 | | 81x=243(x+2) | | (3x+4)(2x-2)= | | 2x-44=x+9 | | 4w+9y+4x+8x-14y+3w= | | (x-4)+66= | | 3t^2+12=0 | | 4x+41x+72=0 | | 3x+26x+35=0 | | 5x-4+3x+6=90 | | 4y+6=6y-3y | | X+4x-32=0 | | ln(4m+2)=ln(5m-7) | | 2B=36+B | | g-8=19 |